Analisis Perilaku Konsumtif Mahasiswa Jurusan Perbankan Syariah IAIN Pekalongan Ditinjau Menurut Ekonomi Islam - Fitri Yulianti (Sahmiyya, 2022)
This study aims to determine the general description of the consumptive behavior of students majoring in Islamic banking at IAIN Pekalongan. This type of research is a qualitative research with a descriptive approach and case studies. The design used in this research is phenomenology. The subjects of this study were students majoring in Islamic banking in the fourth semester. The object of this research is the IAIN Pekalongan campus. In this study, the researcher collected data by using interview, observation, and documentation methods. The techniques used in the validity of the data are extension of participation, persistence of observation, and triangulation. Activities in data analysis, namely data reduction, data display, and conclusion drawing/verification. The results of this study indicate that the consumptive behavior of students majoring in Islamic banking, both from wealthy families and from poor families, in buying goods or products behaves rationally by looking at the benefits compared to brands, advertisements, and promotions. Factors that influence the consumptive behavior of students are motivation and environmental culture on campus. This is in accordance with the provisions of Islam that it is forbidden to live in excess.